Analysis of risk factors for difficult implant removal in children with slipped capital femoral epiphysis treated by cannulated screws - Lei Yang; Lijun Liu; Xiaodong Yang; Xueyang Tang (Frontiers Media S.A., 2024)
IntroductionCannulated screws are widely used in the treatment of slipped capital femoral epiphysis, which can be removed after physeal closure on patient's request. This study aimed to analysis the potential risk factors for difficult removal in children with slipped capital femoral epiphysis treated by cannulated screws.Patients and methodsThis study enrolled 32 hips that had undergone removal of cannulated screws after treatment of slipped capital femoral epiphysis at our department. The primary outcomes were the difficult screw removal. The secondary outcomes were functional outcome assessed by using a modified Harris Hip Score and complications of fractures and surgical site infection. Related risk factors for difficult removal were recorded and analyzed by multivariable logistic regression.ResultsIn total, 32 hips were evaluated, with a mean age of 14.9 ± 1.3 years old (range, 13-19 years). Six (18.8%) hips presented with difficult removal, including 4 cases of screws' slip and 2 breakages. The average implantation time in the difficult removal group (5.7 ± 1.0) was also significantly longer than that in the easily removed group (3.8 ± 0.9, p = 0.001). The mean surgical time in patients with difficult removal was 66.3 ± 11.6 min, which was also significantly longer than that (54.8 ± 8.3) in the other patients (p = 0.008). The duration of screw implantation was an independent risk factor for difficult removal.ConclusionsProlonged screw duration was a predictor for difficult removal in children with slipped capital femoral epiphysis treated by cannulated screws. An early surgery after physeal closure might benefit those with a request for screw removal.